Identification of new DNA markers close to the myotonic dystrophy locus. Issue 2 (February 1991) - Brook, J D; Harley, H G; Walsh, K V; Rundle, S A; Siciliano, M J; Harper, P S; Shaw, D J
Abstract : The most useful markers for the prenatal diagnosis of myotonic dystrophy (DM) are APOC2 and CKM, both of which map proximal to DM. In order to produce other markers useful for DM, we have screened genomic DNA libraries constructed from cell line 20XP3542-1-4, which contains 20 to 30 Mb of human material including APOC2 and CKM. Of 51 human clones identified, seven map to chromosome 17, four to chromosome 8, and nine to chromosome 19, and the remaining 31 were excluded form chromosome 19 but not localised further. Four of the clones from chromosome 19 map distal to CKM and two of these clones (D19S62 and D19S63) are closely linked to DM. Analysis of a family in which a crossover between CKM and DM has occurred shows that neither D19S62 nor D19S63 and DM have recombined, suggesting that D19S62 and D19S63 are either closer to or flanking DM in relation to CKM. Pulsed field gel analysis showed that CKM, D19S62, and D19S63 map to a region of at least 1500 kb.